A fish scale-based bioactive patch and its preparation method and application
Through the decalcification and in situ mineralization treatment of fish scale-based bioactive patches, combined with inorganic active components, the problems of taking into account both the strength and biological activity of tendon patches in the prior art are solved, and efficient tendon repair effects are achieved. It is suitable for Treatment of tendon/ligament injuries.
Patent Information
- Application Number
- CN202111209533.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-18
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-10-18
AI Technical Summary
The existing artificial tendon patches are difficult to take into account high intensity and high biological activity, and the tendons after surgical repair face excessive tension, which leads to difficulty in healing or tearing again.
Fish scale-based bioactive patches are used to combine with inorganic active components after decalcification treatment, retaining the spiral arrangement of multi-layer microstructure, increasing biological activity, and mineralizing in situ under vacuum conditions to form excellent mechanics and biological Active patch.
Fish scale-based bioactive patches have high tensile strength and toughness, can support cell adhesion and proliferation, promote the regeneration of the interface between tendon and tendon bone, improve the repair effect of tendon injuries, and are suitable for the repair of tendon/ligament injuries.
Smart Images

Figure CN115990288B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a fish scale-based bioactive patch and a preparation method thereof, and application of the patch in preparing tendon / ligament repair materials, belonging to the field of biomaterials. Background Art
[0002] Tendon / ligament injuries are a common type of sports medicine disease that often requires surgery to repair. Due to the poor blood supply of the tendon itself and degenerative changes, the tendon repaired after surgery needs to go through a long self-healing process. In addition, since the tendon itself has a certain amount of tension, the tendon after surgery also faces the problem of excessive tension, which can make it difficult for the tendon to heal or even tear again. And in some serious tendon injuries, such as giant rotator cuff tears, the tendon is difficult to suture through surgery, resulting in a gap between the tendon and the bone interface.
[0003] In view of the above problems, the use of tendon patches or tendon grafts for auxiliary treatment of damaged tendons and tendon transplantation is a feasible treatment method. Tendon patches can reduce the tension between tendons and bones, provide attachment points for cell growth, and thus improve the healing of tendons and tendon-bone interfaces. Artificial tendon patches are increasingly favored by clinicians because of their wide sources, avoidance of donor site damage, low immunogenicity, and no risk of infectious diseases. Although a series of preparation methods for artificial tendon patches have been proposed in recent years, it is difficult for existing artificial tendon patches to have both high strength and high biological activity, and this problem remains to be solved.
[0004] The exoskeletons of some natural organisms have good mechanical properties, such as fish scales, shells, lobster shells, etc. Among them, fish scales are a high-strength flexible natural material, which has excellent tensile strength due to its special spirally arranged multi-layer microstructure. At present, there are few reports in China on the preparation of biomaterials based on natural materials with special microstructures. This type of natural material can be treated by appropriate methods to improve its biological activity while retaining the multi-layer microstructure, and can be used to prepare artificial tendon patches with both high strength and high biological activity. Summary of the invention
[0005] In view of the above problems, the present invention provides a fish scale-based bioactive patch for tendon / ligament repair and a preparation method thereof.
[0006] On the one hand, the present invention provides a fish scale-based bioactive patch, which comprises a fish scale base and an inorganic active component; the fish scale-based bioactive patch has a spirally arranged multi-layer microstructure, and each layer is formed by in-situ mineralization of collagen fibers of the fish scale base and the inorganic active component; the fish scale base is a decalcified natural fish scale (the decalcification time is controlled to the extent that the calcified layer is just completely removed and the collagen fibers in the fish scale are fully exposed and not damaged, and the decalcified fish scale base has a spiral staircase-like microstructure composed of oriented collagen fiber bundles, reaching The optimal mechanical properties are achieved, and the collagen fiber bundles are fully exposed, which can be used as mineralization sites, facilitating subsequent in situ mineralization treatment); the inorganic active components account for 0 to 60 wt% of the fish scale-based bioactive patch. The addition of inorganic active components is beneficial to improving the bioactive properties of the patch, so that the patch can release active inorganic ions such as calcium and silicon, locally regulate stem cell differentiation and angiogenesis, and can induce the regeneration of tendon-bone interface transition tissue, thereby improving the repair of tendon defects. The optimal content of inorganic active components in the bioactive patch is 20 to 42 wt%.
[0007] In the present invention, the fish scale-based bioactive patch retains the original spirally arranged multi-layer microstructure of natural fish scales, and each layer is composed of collagen fibers and inorganic active components (or does not contain inorganic active components), and is arranged in a spiral shape according to a certain angle. Among them, the content of the inorganic active component is controlled within the above range, which can avoid contact with high-concentration solutions to cause a large amount of hydrolysis of collagen inside the fish scales, thereby reducing the mechanical properties and being unable to withstand the tension of the tendon.
[0008] Preferably, before decalcification, the natural fish scale is a biological fish scale, preferably a silver carp scale, a carp scale, a grass carp scale, or a black carp scale, and most preferably a black carp scale. Fresh natural fish scales are washed and stripped of fascia tissue, and then immersed in a decalcification solution for decalcification to form a fish scale base.
[0009] Preferably, the decalcification liquid used for decalcification is at least one of EDTA decalcification liquid, formic acid aqueous solution, and hydrochloric acid aqueous solution, with a concentration of 0.1 to 0.5 mol / L; the decalcification time is 3 to 14 days. According to different fish scales, the decalcification time needs to be controlled so that the calcification layer is just completely removed and the collagen fibers in the fish scale microstructure are fully exposed and not damaged. At this time, the decalcified fish scale base has a spiral staircase-shaped microstructure composed of oriented collagen fiber bundles, achieving the best mechanical properties; and the full exposure of the collagen fiber bundles can be used as a mineralization site, which is convenient for subsequent in-situ mineralization treatment. Specifically, the decalcification liquid used for silver carp scales is at least one of EDTA decalcification liquid, formic acid aqueous solution, and hydrochloric acid aqueous solution, with a concentration of 0.3 to 0.5 mol / L, and the decalcification time is 10 to 14 days. The decalcification liquid used for carp scales is at least one of EDTA decalcification liquid, formic acid aqueous solution, and hydrochloric acid aqueous solution, with a concentration of 0.3-0.5 mol / L, and the decalcification time is 10-14 days. The decalcification liquid used for grass carp scales is at least one of EDTA decalcification liquid, formic acid aqueous solution, and hydrochloric acid aqueous solution, with a concentration of 0.3-0.5 mol / L, and the decalcification time is 6-10 days. The decalcification liquid used for black carp scales is at least one of EDTA decalcification liquid, formic acid aqueous solution, and hydrochloric acid aqueous solution, with a concentration of 0.3-0.5 mol / L, and the decalcification time is 3-7 days.
[0010] Preferably, the inorganic active component is at least one of calcium silicate, magnesium silicate, zinc silicate, manganese silicate, calcium phosphate, magnesium phosphate, zinc phosphate and manganese phosphate.
[0011] Preferably, the maximum tensile force of the fish scale-based bioactive patch is 15-145 MPa; the Young's modulus of the fish scale-based bioactive patch is 350-770 MPa; the toughness of the fish scale-based bioactive patch is 1-18 MJ·m -3 .
[0012] On the other hand, the present invention provides a method for preparing a fish scale-based bioactive patch, wherein the decalcified natural fish scale is immersed in a mineralizing solution containing metal cations for 4 to 12 hours under vacuum conditions, and then washed and dried to obtain the fish scale-based bioactive patch.
[0013] The present invention provides a method for preparing a fish scale-based bioactive patch, which can combine one or more inorganic active components with the collagen fibers of the fish scale itself while maintaining good mechanics of the patch to improve the biological activity.
[0014] Preferably, the metal cations in the mineralization solution containing metal cations are at least one of calcium ions, magnesium ions, manganese ions, and zinc ions (preferably at least two of calcium ions, magnesium ions, manganese ions, and zinc ions); the concentration range of the metal cations in the mineralization solution containing metal cations is 0.1 to 2M.
[0015] Preferably, the metal cation source in the mineralization solution containing metal cations is at least one of calcium silicate, magnesium silicate, manganese silicate, zinc silicate, calcium phosphate, magnesium phosphate, manganese phosphate and zinc phosphate.
[0016] Preferably, the vacuum degree of the vacuum condition is less than 500Pa.
[0017] In yet another aspect, the present invention provides a use of a fish scale-based bioactive patch in the preparation of a tendon / ligament repair material.
[0018] Beneficial effects:
[0019] In the present invention, the fish scale-based bioactive patch is composed of a fish scale base and an inorganic active component (or does not contain an inorganic active component), has good tensile strength and biological activity, can support cell adhesion and proliferation, stimulate the differentiation and phenotype maintenance of a variety of cells derived from tendon-bone tissue, and is expected to be used for the repair of tendon / ligament injuries. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a flow chart for preparing a calcium silicate-modified fish scale-based bioactive patch according to one embodiment of the present invention;
[0021] Figure 2 (a) is a schematic diagram of the microstructure of a natural fish scale and a scanning electron microscope image (O-FS) of a cross section, (b), (c), (d), (e), and (f) are schematic diagrams of the microstructure of the fish scale substrate after decalcification without inorganic active components in Examples 1-5 and scanning electron microscope images (i.e., 0FS, 0.2CS-FS, 0.5CS-FS, 0.75CS-FS, and 1CS-FS), (g) is a high-resolution transmission electron microscope image (1CS-FS) of the fish scale-based bioactive patch modified with calcium silicate in Example 5, and (h) is an energy spectrum analysis (1CS-FS) of the fish scale-based bioactive patch modified with calcium silicate in Example 5;
[0022] Figure 3 Material mechanical properties of natural tendon (Tendon), natural fish scale (O-FS), various fish scale-based bioactive patches (0FS, 0.2CS-FS, 0.5CS-FS, 0.75CS-FS, 1CS-FS) are tested. (a) is the maximum tensile strength, (b) is the toughness, and (c) is the Young's modulus.
[0023] Figure 4a-4c and Figure 5The growth of rabbit bone marrow mesenchymal stem cells, rabbit chondrocytes, and rabbit tendon stem cells cultured on various fish scale-based bioactive patches; (4a) CCK-8 method was used to detect the cell viability of rabbit bone marrow mesenchymal stem cells cultured on patches of each group for 1, 4, and 7 days; (4b) CCK-8 method was used to detect the cell viability of rabbit chondrocytes cultured on patches of each group for 1, 4, and 7 days; (4c) CCK-8 method was used to detect the cell viability of rabbit tendon stem cells cultured on patches of each group for 1, 4, and 7 days; (5d) confocal microscopy images and scanning electron microscopy images of rabbit bone marrow mesenchymal stem cells after inoculation on patches of each group for 24 hours; (5e) confocal microscopy images and scanning electron microscopy images of rabbit chondrocytes after inoculation on patches of each group for 24 hours; (5f) confocal microscopy images and scanning electron microscopy images of rabbit tendon stem cells after inoculation on patches of each group for 24 hours;
[0024] Figure 6a-6c The expression of genes related to the directional differentiation of various cells stimulated by various fish scale-based bioactive patches was detected. The detected genes were the expression of osteogenic differentiation-related genes (Runx2, Opn, Col-1, Ocn) in rabbit bone marrow mesenchymal stem cells (BMSCs), the expression of cartilage phenotype-related genes (Sox9, N-Cadh, Col-2, Aggrecan) in rabbit chondrocytes, and the expression of tendinogenic differentiation-related genes (Dcn, Tnc, Col-1, Bgn) in rabbit tendon stem cells (TSPCs); Figure 6a-6c It can be seen that the three groups of 0.5CS-FS, 0.75CS-FS, and 1CS-FS can all stimulate the expression of genes related to differentiation of different types of cells. Thermogravimetric analysis shows that the contents of inorganic components corresponding to these three groups are 20.17wt%, 28.07wt%, and 41.26wt%, respectively (Examples 3, 4, and 5). It is concluded that the optimal range of the inorganic content component is 20 to 42wt%.
[0025] Figure 7 (a) is a schematic diagram of the model for modeling and repair of rabbit rotator cuff tendon injury, (b), (c), and (d) are intraoperative photographs of using fish scale-based bioactive patches (0.5CS-FS) to repair rabbit rotator cuff injuries. DETAILED DESCRIPTION
[0026] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0027] In the present disclosure, the fish scale-based bioactive patch is prepared based on natural fish scales, which has a spirally arranged multi-layer microstructure, each layer of which is composed of collagen fibers combined with inorganic active components (or does not contain inorganic active components, see Figure 2(b), (c), (d), (e), (f) in the figure. Figure 2 As can be seen in (g), calcium silicate particles, as inorganic active components in the patch, are uniformly mineralized on the surface of the collagen fibers.
[0028] The maximum tensile force of the fish scale-based bioactive patch tested by a universal mechanical testing machine is 15-145 MPa. The Young's modulus of the fish scale-based bioactive patch tested by a universal mechanical testing machine is 350-770 MPa. The toughness of the fish scale-based bioactive patch tested by a universal mechanical testing machine is 1-18 MJ·m -3 Through material mechanics experiments, it was found that the maximum tensile strength and toughness of the fish scale-based bioactive patch exceeded those of natural tendons, fully meeting the needs of tendon repair, and the Young's modulus was similar to that of tendon tissue, indicating that the fish scale-based bioactive patch has good mechanical properties.
[0029] In an optional embodiment, the bioactivity of the patch is further regulated by regulating the content of inorganic active components in the fish scale-based bioactive patch. The mass percentage of inorganic active components in the fish scale-based bioactive patch is preferably 0 to 60wt%, and more preferably about 20 to 42wt%. In some embodiments, mineralization using 0.5M mineralizing liquid can achieve a mineralization amount of about 20%. The fish scale-based bioactive patch has excellent mechanical properties and biological activity, can stimulate the differentiation of multiple cells, can regulate tendon regeneration, repair tendon injuries, and improve the healing and biomechanics of the tendon-bone interface. Through in vitro cell experiments, it was found that the fish scale-based bioactive patch of the present invention can promote cell adhesion and growth. Although the patch with a higher calcium silicate content has a certain inhibitory effect on cell proliferation, it can also support long-term cell proliferation. In vivo animal experiments found that the fish scale-based bioactive patch can promote the regeneration of the tendon-bone interface, as well as tendon injury repair, and improve the biomechanical properties of damaged tendons. In summary, the fish scale-based bioactive patch of the present invention can withstand the tension of the tendon injury site, is more conducive to the adhesion and proliferation of various cells, has good biological activity in promoting the regeneration of tendons and tendon-bone interfaces in vivo, and is suitable for the repair of tendon / ligament injuries.
[0030] like Figure 1 As shown, the following is an exemplary description of the preparation method of the fish scale-based bioactive patch of the present invention. The method successfully prepares fish scale-based bioactive patches with different inorganic active component contents by using a new method of vacuum-induced in-situ mineralization. The fish scale-based bioactive patch is used for the repair of tendon injuries and has not only excellent mechanical properties but also good biological activity.
[0031] The natural fish scales are pretreated. The natural fish scales can be silver carp scales, carp scales, grass carp scales, black carp scales, etc., preferably black carp scales. Fresh fish scales are washed with running water, and after peeling off the fascia, epidermis, muscle and other organic tissues on the surface of the scales, they are immersed in a decalcification solution for decalcification (decalcification can be achieved at room temperature, for example, 18-28° C.) to form a fish scale base. The decalcification solution can be at least one of EDTA decalcification solution, formic acid aqueous solution, and hydrochloric acid aqueous solution, and the concentration can be 0.1-0.5 mol / L. The decalcification treatment time can be 3-14 days. The prepared fish scale base, if no subsequent mineralization step is performed, is a fish scale-based bioactive patch that does not contain inorganic active components.
[0032] Prepare a mineralizing solution. According to the composition of the inorganic active components in the fish scale-based bioactive patch, prepare a cationic solution of a metal source containing a mineralized substance and its corresponding anionic solution of a certain concentration. The cationic solution containing the metal source of the mineralized substance includes at least one of the water-soluble inorganic salts of calcium, magnesium, manganese, and zinc and the corresponding hydrates of the inorganic salts, and the concentration range of the cationic solution can be 0.1 to 2M. The anionic solution containing the mineralized substance and its corresponding anionic solution includes at least one of the water-soluble inorganic salts containing silicate and phosphate and the corresponding hydrates of the inorganic salts. The concentration range of the anionic solution can be 0.1 to 2M, which is consistent with the concentration of the cationic solution.
[0033] In-situ mineralization treatment: The fish scale patch substrate is immersed in cationic and anionic solutions in a vacuum condition, and vacuum-induced in-situ mineralization is performed to modify inorganic active components on the sheet layer of the fish scale substrate. Drying: After the mineralization is completed, the fish scale substrate is washed and dried twice to obtain a fish scale-based bioactive patch.
[0034] When calcium silicate is used as the inorganic active component in the fish scale-based bioactive patch, the specific operation is as follows: the decalcified fish scale base is placed in a centrifuge tube, soaked in calcium nitrate solution (0.1M-2M), and the centrifuge tube is placed in a vacuum oven and kept under vacuum for 4-10 hours. The fish scale base is taken out, the residual droplets on the surface are gently wiped off, and freeze-dried at -10 to -50°C for 4-10 hours to obtain the freeze-dried fish scale base. The freeze-dried fish scale base is spread on a flat plate, and a sodium silicate solution (0.1M-2M) is dripped on the surface to soak. The concentrations of the selected calcium nitrate solution and sodium silicate solution must be consistent. The fish scale base with the sodium silicate solution dripped is placed in a vacuum oven and kept under vacuum (e.g. <500Pa) for 4-12 hours. Then the fish scale base is taken out, the residual droplets on the surface are gently wiped off, and dried (e.g., placed in a 60°C oven for 1-3 hours). Then, the fish scale base is taken out and soaked in deionized water for 30-60 minutes to remove nitrate ions and sodium ions, and then placed in an oven for secondary drying (for example, secondary drying in an oven at 60° C. for 1-3 hours) to obtain a calcium silicate-modified fish scale-based bioactive patch. In this process, the calcium silicate particles are in situ mineralized on the collagen fibers of the fish scale layer.
[0035] The present invention firstly uses vacuum-induced mineralization to uniformly modify inorganic active components such as calcium silicate on the collagen fibers in the fish scales. Since the carbonyl and carboxyl groups on the collagen fibers can produce chelation with metal cations such as calcium ions, they can become mineralization sites for in-situ mineralization. Then, metal cations such as calcium ions combine with anions such as silicate to form mineralized substances, so that the collagen fibers can be in-situ mineralized and combined with inorganic active components such as calcium silicate. In particular, the amount of mineralization is controlled within a certain range, and the spirally arranged multi-layer microstructure of the fish scales will not be destroyed, so that the fish scale-based bioactive patch can still maintain good mechanical properties. Then, the biological activity of calcium silicate in the patch is used to regulate the differentiation and proliferation of various cells, as well as the regeneration of complex tissues at the tendon and tendon-bone interface in the body, so that the fish scale-based bioactive patch has both good mechanical properties and biological activity.
[0036] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0037] Example 1
[0038] Fresh black carp scales were washed with running water, and the fascia, epidermis, muscle and other tissues on the surface of the scales were stripped off, and then immersed in EDTA decalcification solution (0.4-0.5 mol) for decalcification for 7 days. After decalcification, a large amount of deionized water was used to wash and dry the scale-based bioactive patch without inorganic components, named OFS.
[0039] Example 2
[0040] Fresh black carp scales were washed with running water, and the fascia, epidermis, muscle and other tissues on the surface of the scales were peeled off. Then, the scales were immersed in EDTA decalcification solution (0.4-0.5moL) for decalcification for 7 days. Calcium nitrate solution (concentration of 0.2M) and sodium silicate solution (concentration of 0.2M) were prepared for mineralization. The decalcified scale base was placed in a centrifuge tube and immersed in calcium nitrate solution. The centrifuge tube was placed in a vacuum oven and kept under vacuum for 6 hours. Then, the scale base was taken out, the calcium nitrate solution droplets remaining on the surface were gently wiped off, and freeze-dried for 4 hours. The freeze-dried scale base was spread on a flat plate, and a sodium silicate solution with the same concentration as the calcium nitrate solution was added to the surface. Then, the scale base was placed in a vacuum oven and kept under vacuum for 6 hours. Then, the scale base was taken out, the droplets remaining on the surface were gently wiped off, and it was placed in a 60°C oven for drying for 2 hours and then taken out. The scale base was soaked in deionized water for 30 minutes to remove residual nitrate ions and sodium ions. Then, it was placed in a 60°C oven for a second drying for 2 hours to obtain a calcium silicate mineralized fish scale-based bioactive patch. Thermogravimetric analysis showed that the inorganic component content was 16.89%, and it was named 0.2CS-FS.
[0041] Example 3
[0042] Fresh black carp scales were washed with running water, and the fascia, epidermis, muscle and other tissues on the surface of the scales were peeled off. Then, the scales were immersed in EDTA decalcification solution (0.4-0.5moL) for decalcification for 7 days. Calcium nitrate solution (concentration of 0.5M) and sodium silicate solution (concentration of 0.5M) were prepared for mineralization. The decalcified scale base was placed in a centrifuge tube, soaked in calcium nitrate solution, and the centrifuge tube was placed in a vacuum oven for 6 hours under vacuum. Then, the scale base was taken out, the calcium nitrate solution droplets remaining on the surface were gently wiped off, and freeze-dried for 4 hours. The freeze-dried scale base was spread on a flat plate, and a sodium silicate solution with the same concentration as the calcium nitrate solution was added to the surface. Then, the scale base was placed in a vacuum oven for 6 hours under vacuum. Then, the scale base was taken out, the droplets remaining on the surface were gently wiped off, and it was placed in a 60°C oven for drying for 2 hours before being taken out. The fish scale substrate was soaked in deionized water for 30 minutes to remove residual nitrate ions and sodium ions, and then placed in a 60°C oven for a second drying for 2 hours to obtain a fish scale-based bioactive patch modified with calcium silicate mineralization. Thermogravimetric analysis showed that the inorganic component content was 20.17%, and it was named 0.5CS-FS.
[0043] Example 4
[0044] Fresh black carp scales were washed with running water, and the fascia, epidermis, muscle and other tissues on the surface of the scales were peeled off, and then immersed in EDTA decalcification solution (0.4-0.5moL) for decalcification for 7 days. Calcium nitrate solution (concentration of 0.75M) and sodium silicate solution (concentration of 0.75M) were prepared for mineralization. The decalcified scale base was placed in a centrifuge tube and soaked in calcium nitrate solution. The centrifuge tube was placed in a vacuum oven and kept under vacuum for 6 hours. Then the scale base was taken out, the calcium nitrate solution droplets remaining on the surface were gently wiped off, and freeze-dried for 4 hours. The freeze-dried fish scale substrate was spread on a flat plate, and a sodium silicate solution with the same concentration as the calcium nitrate solution was dripped on the surface. The fish scale substrate was then placed in a vacuum oven and kept in a vacuum state for 6 hours. The fish scale substrate was then taken out, and the residual droplets on the surface were gently wiped off. The fish scale substrate was placed in a 60°C oven for drying for 2 hours and then taken out. The fish scale substrate was soaked in deionized water for 30 minutes to remove the residual nitrate ions and sodium ions, and then placed in a 60°C oven for secondary drying for 2 hours to obtain a fish scale-based bioactive patch modified with calcium silicate mineralization. Thermogravimetric analysis showed that the inorganic component content was 28.07%, and it was named 0.75CS-FS.
[0045] Example 5
[0046] Fresh black carp scales were washed with running water, and the fascia, epidermis, muscle and other tissues on the surface of the scales were peeled off. Then, the scales were immersed in EDTA decalcification solution (0.4-0.5moL) for decalcification for 7 days. Calcium nitrate solution (concentration of 1M) and sodium silicate solution (concentration of 1M) were prepared for mineralization. The decalcified scale base was placed in a centrifuge tube and soaked in calcium nitrate solution. The centrifuge tube was placed in a vacuum oven and kept under vacuum for 6 hours. Then, the scale base was taken out, the calcium nitrate solution droplets remaining on the surface were gently wiped off, and freeze-dried for 4 hours. The freeze-dried scale base was spread on a flat plate, and a sodium silicate solution with the same concentration as the calcium nitrate solution was added to the surface. Then, the scale base was placed in a vacuum oven and kept under vacuum for 6 hours. Then, the scale base was taken out, the droplets remaining on the surface were gently wiped off, and it was placed in a 60°C oven for drying for 2 hours and then taken out. The scale base was soaked in deionized water for 30 minutes to remove residual nitrate ions and sodium ions. Then, it was placed in a 60°C oven for a second drying for 2 hours to obtain a fish scale-based bioactive patch modified with calcium silicate mineralization. Thermogravimetric analysis showed that the inorganic component content was 41.26%, and it was named 1CS-FS.
[0047] The performance evaluation of fish scale-based bioactive patches includes mechanical properties, in vitro bioactivity, and the ability to repair tendon injuries in animals. The microstructure and composition changes of fish scale bioactive patches were characterized by scanning electron microscopy and high-resolution transmission electron microscopy.
[0048] from Figure 2 It can be seen that the fish scale-based bioactive patch prepared by the present invention, i.e., Examples 1-4, still retains the spirally arranged layered microstructure, each layer is composed of collagen fibers and inorganic active components, and calcium silicate particles are uniformly mineralized on the collagen fibers, with a particle size of about 40 nm. As the concentration of the mineralizing solution increases, the deposition amount of calcium silicate particles increases.
[0049] from Figure 3 It can be seen that the maximum tensile strength and toughness of most fish scale-based bioactive patches are higher than those of natural tendons, showing good mechanical properties. Only the maximum tensile strength and toughness of 1CS-FS in Example 4 are slightly lower than those of natural tendons. This shows that within a certain range of mineralization, fish scale-based bioactive patches can still maintain good mechanical properties. The Young's modulus of fish scale-based bioactive patches is roughly similar to that of natural tendons, which can avoid the problem of difficult tendon healing caused by stress shielding.
[0050] Fish scale-based bioactive patches have cytocompatibility and differentiation regulatory effects on a variety of cells, such as bone marrow mesenchymal stem cells (BMSCs), chondrocytes, and tendon stem cells (TSPCs).
[0051] from Figure 4a-4c and Figure 5It can be seen that the fish scale-based bioactive patches of Examples 1-4 can well support the adhesion and proliferation of various cells, and the cells show an extended morphology without a curled cell morphology. The fish scale-based bioactive patches can also support the proliferation of rabbit BMSCs, rabbit chondrocytes and rabbit TSPCs. The cells show obvious cell proliferation after being inoculated on the patches for 1, 4 and 7 days, indicating that the fish scale-based bioactive patches have good cell compatibility.
[0052] from Figure 6a-6c It can be seen that the fish scale-based bioactive patch can stimulate the expression of genes related to directional differentiation or phenotype maintenance of various cells, indicating that it has diverse biological activities. It can not only regulate the differentiation of various cells derived from tendons, but also has biological activity for cells derived from bones and cartilage in other parts.
[0053] from Figure 7 It can be seen that the fish scale-based bioactive patch (1CS-FS) can be used for tendon repair surgery. The patch is cut into a size of 0.5×1cm. The patch has good mechanical properties and can be well transplanted into the injured site of the rabbit rotator cuff tendon through surgery, bridging the damaged supraspinatus tendon and bone well.
[0054] From the above, it can be seen that the fish scale-based bioactive patch has excellent mechanical properties and bioactivity, indicating that the fish scale-based bioactive patch can be used in clinical tendon-related injuries.
[0055] Example 6
[0056] Fresh carp scales were washed with running water, and the fascia, epidermis, muscle and other tissues on the surface of the scales were peeled off, and then immersed in EDTA decalcification solution (0.4-0.5moL) for decalcification for 10 days. Magnesium chloride solution (concentration of 0.5M) and sodium silicate solution (concentration of 0.5M) were prepared for mineralization, and the decalcified scale base was placed in a centrifuge tube and soaked in magnesium chloride solution. The centrifuge tube was placed in a vacuum oven and kept under vacuum for 6 hours. Then the scale base was taken out, the residual magnesium chloride solution droplets on the surface were gently wiped off, and freeze-dried for 5 hours. The freeze-dried fish scale base is spread on a flat plate, and a sodium silicate solution with the same concentration as the magnesium chloride solution is added to the surface. The fish scale base is then placed in a vacuum oven and kept under vacuum for 8 hours. The fish scale base is then taken out, and the residual droplets on the surface are gently wiped off. The base is placed in a 60°C oven for drying for 2 hours and then taken out. The fish scale base is soaked in deionized water for 30 minutes to remove residual chloride ions and sodium ions, and then placed in a 60°C oven for a second drying for 2 hours to obtain a fish scale-based bioactive patch modified with magnesium silicate mineralization.
[0057] Example 7
[0058] Fresh carp scales are washed with running water, and the fascia, epidermis, muscle and other tissues on the surface of the scales are peeled off, and then immersed in EDTA decalcification solution (0.4-0.5moL) for decalcification for 10 days. A magnesium chloride / calcium chloride mixed solution (the concentration in the solution is: magnesium chloride concentration is 0.2M, calcium chloride concentration is 0.3M), and a sodium silicate solution concentration is 0.5M) is prepared for mineralization. The decalcified fish scale base is placed in a centrifuge tube and soaked in a magnesium chloride and calcium chloride mixed solution. The centrifuge tube is placed in a vacuum oven and kept under vacuum for 6 hours. Then the fish scale base is taken out, the residual mixed solution droplets on the surface are gently wiped off, and freeze-dried for 5 hours. The freeze-dried fish scale base is spread on a flat plate, and a sodium silicate solution is added to the surface. The fish scale base is then placed in a vacuum oven and kept under vacuum for 8 hours. The fish scale base is then taken out, and the residual droplets on the surface are gently wiped off. The fish scale base is placed in a 60°C oven for drying for 2 hours and then taken out. The fish scale base is soaked in deionized water for 30 minutes to remove residual nitrate ions and sodium ions, and then placed in a 60°C oven for a second drying for 2 hours to obtain a fish scale-based bioactive patch modified with a mixed mineralization of magnesium silicate / calcium silicate.
[0059] Example 8
[0060] Fresh silver carp scales were washed with running water, and after peeling off the fascia, epidermis, muscle and other tissues on the surface of the scales, they were immersed in EDTA decalcification solution (0.4-0.5moL) for decalcification for 14 days. Manganese chloride solution (concentration of 1.5M) and sodium silicate solution (concentration of 1.5M) were prepared for mineralization. The decalcified scale base was placed in a centrifuge tube and soaked in the manganese chloride mixed solution. The centrifuge tube was placed in a vacuum oven and kept under vacuum for 6 hours. Then the scale base was taken out, the residual mixed solution droplets on the surface were gently wiped off, and freeze-dried for 5 hours. The freeze-dried fish scale base was spread on a flat plate, and a sodium silicate solution was added to the surface. The fish scale base was then placed in a vacuum oven and kept under vacuum for 8 hours. The fish scale base was then taken out, and the residual droplets on the surface were gently wiped off. The fish scale base was placed in a 60°C oven for drying for 2 hours and then taken out. The fish scale base was soaked in deionized water for 30 minutes to remove residual nitrate ions and sodium ions, and then placed in a 60°C oven for a second drying for 2 hours to obtain a fish scale-based bioactive patch modified with manganese silicate mineralization.
[0061] Example 9
[0062] Fresh grass carp scales were washed with running water, and the fascia, epidermis, muscle and other tissues on the surface of the scales were stripped off, and then immersed in EDTA decalcification solution (0.4-0.5moL) for decalcification for 7 days. A magnesium chloride / calcium chloride mixed solution (the concentration of magnesium chloride in the solution was 0.6M, the concentration of calcium chloride was 0.6M), and a sodium phosphate solution concentration was 1.2M was prepared for mineralization. The decalcified fish scale base was placed in a centrifuge tube and soaked in the manganese chloride mixed solution. The centrifuge tube was placed in a vacuum oven and kept under vacuum for 6 hours. Then the fish scale base was taken out, the residual mixed solution droplets on the surface were gently wiped off, and freeze-dried for 5 hours. The freeze-dried fish scale base is spread on a flat plate, sodium phosphate solution is added to the surface, and then the fish scale base is placed in a vacuum oven and kept under vacuum for 8 hours. The fish scale base is then taken out, the residual droplets on the surface are gently wiped off, and the base is placed in a 60°C oven for drying for 2 hours and then taken out. The fish scale base is soaked in deionized water for 30 minutes to remove residual chloride ions and sodium ions, and then placed in a 60°C oven for a second drying for 2 hours to obtain a calcium phosphate / magnesium phosphate mixed mineralized modified fish scale-based bioactive patch.
Claims
1. A fish scale-based bioactive patch, characterized in that: The fish scale-based bioactive patch comprises a fish scale base and an inorganic active component; the fish scale-based bioactive patch has a spirally arranged multi-layer microstructure, and each layer is formed by in-situ mineralization and combination of collagen fibers of the fish scale base and the inorganic active component; the fish scale base is a decalcified natural fish scale; fresh natural fish scales are washed and the fascia tissue is stripped, and then immersed in a decalcification solution for decalcification to form a fish scale base; the decalcification solution used for decalcification is an EDTA decalcification solution with a concentration of 0.1 to 0.5 mol / L; the decalcification time is 3 to 14 days; the mass percentage of the inorganic active component in the fish scale-based bioactive patch is 0 to 28.07wt%, and is not 0.
2. The fish scale-based bioactive patch according to claim 1, characterized in that: The mass percentage of the inorganic active component in the fish scale-based biologically active patch is 20 to 28.07 wt %.
3. The fish scale-based bioactive patch according to claim 1, characterized in that: Before decalcification, natural fish scales are fish biological scales.
4. The fish scale-based bioactive patch according to claim 3, characterized in that: The natural fish scales are silver carp scales, carp scales, grass carp scales or black carp scales.
5. The fish scale-based bioactive patch according to claim 1, characterized in that: The inorganic active component is at least one of calcium silicate, magnesium silicate, zinc silicate, manganese silicate, calcium phosphate, magnesium phosphate, zinc phosphate and manganese phosphate.
6. The fish scale-based bioactive patch according to any one of claims 1 to 5, characterized in that: The maximum tensile force of the fish scale-based bioactive patch is 15-145 MPa, the Young's modulus is 350-770 MPa, and the toughness is 1-18 MJ·m -3 .
7. A method for preparing a fish scale-based bioactive patch according to any one of claims 1 to 6, characterized in that: Under vacuum conditions, the decalcified natural fish scales are immersed in a solution containing metal cations and a corresponding anion solution for 4 to 12 hours respectively, and then washed and dried to obtain the fish scale-based bioactive patch; The metal cation in the cationic solution is at least one of calcium ion, magnesium ion, manganese ion, and zinc ion; the metal cation concentration range in the cationic solution is 0.1 to 2M; the anionic solution includes at least one of a water-soluble inorganic salt containing silicate and phosphate and a corresponding hydrate of the inorganic salt; the concentration range of the anionic solution can be 0.1 to 2M.
8. The preparation method according to claim 7, characterized in that: The vacuum degree of the vacuum condition is less than 500Pa.
9. Use of the fish scale-based bioactive patch according to any one of claims 1 to 6 in the preparation of tendon repair materials and ligament repair materials.
